Design and implementation of fuzzy-based PID controller - Salami, Momoh Jimoh Eyiomika; Bulale I., Yusuf (2002)
controller is widely used in many industrial applications due to its simplicity in StmctllIe and ease of design. However, it is difficult to achieve .the desired control performance in the presence of unknown nonlinearities, time delays, disturbances as well as changes in system parameters. Consequently several PID models have been suggested so at to alleviate these effects on the performance of the PID controllers. One such method is based on fuzzy logic technique which is considered much more appropri.ate when precise mathematical formulation is infeasible or difficult to achieve. Furthermore, some applications such as semiconductor packaging, computer disk drives, and ultra-precision machining require a fast and high precision processing. Consequently, there is the need to consider digital signal processor (DSI?)- based fuzzy PID for use in such applications. Design and implementation of such technique is proposed in this paper. Results of simulation studies haw demonstrated the feasibility of this controller since: it produces fast response with smooth motion control.